Regulatory guidance on toxicity testing of pharmaceuticals: ICH - Kapeghian, John (Henry Stewart Talks, 2009)
History of drug safety regulations, Who is the ICH?, Harmonization of toxicity testing guidelines: why?, What guidelines currently exist and how are they applied to toxicity testing, How guidelines are harmonized through the ICH process, What safety guidelines are typically followed in an IND, Issues and future considerations for harmonized safety testing guidelines worldwide